Sistem Informasi Manajemen Penggajian ASN (Simgaji) Pada Pemerintah Daerah Kabupaten Indramayu - Putri, Maysa Rewandi; Suyaman, Dede Jajang (Peneliti.net, 2024)
The purpose of this research is to find out the system and procedure for issuing payroll for State Civil Apparatuses with application-based payroll management, namely the Payroll Management Information System and Payroll Compensation Services for Assistants. By implementing payroll management based on an information system, of course, it will form the Indramayu Regency Regional Government organization to make a new breakthrough in the payroll system for State Civil Apparatuses, numbering thousands of which can be paid on time every month without any problems. The payroll information system prevents errors when calculating payroll expenditures, does not require a lot of human resources, and does not take a long time, achieves accurate staffing information and financial data by utilizing SIMGAJI, provides a database of human and financial resources for each state civil apparatus and faster presentation of performance reports to be submitted to the Ministry of Finance of the Republic of Indonesia through an integrated application as a basis for distributing the General Allocation Fund (DAU) to local governments, on the method that has been prepared by the central government for the monthly salary budget in the region. The process of issuing ASN salaries to the Regional Government of Indramayu Regency starts from the arrangement, input, process, to the result/output in the form of a list of ASN salaries which will be used as the basis for paying ASN salaries every month.